Analyzing the role of digital/non-digital technology entrepreneur typology in external factors’ influence on venture launch decisions - Ram Subramaniam; Murali Sambasivan (Journal of Innovation and Entrepreneurship)
Abstract Digital technology entrepreneurs (DTEs) have emerged at the forefront of entrepreneurial research and practice, driven by the rapid pace of innovation, global connectivity, on-demand scalability, and the disruptive potential of digital technologies across industries. This study investigates the influence of three macro-level external factors—access to funding (FN), access to human capital (HC), and institutional support (IN)—on the likelihood of venture launch (VL). An online survey of 218 entrepreneurs from around the world captured perceived magnitudes of FN, HC, and IN within their respective ecosystems, along with the corresponding likelihood of launching a venture. The sample included 108 DTEs and 110 non-DTEs. We tested the hypotheses using a regression model. Empirical findings highlight the intricate interplay among external factors in entrepreneurial ecosystems. Notably, dominant factors such as funding access may trigger the influence of latent ones, such as human capital. The strength and effect of these factors vary by entrepreneurial typology. Results show that the impact of external conditions on venture launch decisions differs between DTEs and non-DTEs, underscoring the importance of factor complementarity in shaping entrepreneurial outcomes.